Social Media Platform Slang Language: Learning Indonesian as a Language of Communication in Daily Conversation - Mayrita, Hastari; Indah Sari, Ayu Puspita; Ernawati, Yeni; Wahyuni, Sri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to identify and interpret slang messages used in daily conversations, especially those used among young people, and create material content on the social media platform 'Bahasa Gaul-Bahasa Indonesia.' Instagram is the social media platform used to include the material content of the slang findings from this research. So, the results of the research can be used as a medium for speakers to learn Indonesian, especially the language of daily communication, with the selection of appropriate diction so that communication becomes more efficient and effective. The method used in this research is a qualitative method with a case study approach. The data collection technique used was the document technique. The data is in the form of recordings of the slang vocabulary used by Palembang speakers. The observed utterances were taken randomly for 30 minutes, either in situations in the canteen, in class, with relatives, or in the researcher's neighborhood. The number of utterances obtained was 107 utterances, with 40 speakers. The data analysis technique uses semiotic techniques with a pragmatic approach. The findings in this study are 100 slang words used in Palembang Sari-Sari conversations by Palembang speakers who are the subjects of this study. Then, the results of the findings and analysis are used as content on the Instagram platform of Bahasa Gaul-Bahasa Palembang-Bahasa Indonesia (BBG-Belajar Bahasa Gaul), with the Instagram name @belajar_bahasa_gaul.